PERTANGGUNGJAWABAN PIDANA KURATOR BERDASARKAN PRINSIP INDEPENDENSI MENURUT HUKUM KEPAILITAN - Sriti Hesti Astiti (Yuridika, 2017)
This article aimed to criticize the juridical basis of scope of crime mentioned on Law Number 37 of 2004, focuses on criminal responsibility of a curator based on independence principle of bankruptcy law. Essentially, bankruptcy is a part of civil law. However, some bankruptcy cases eventually evolve into criminal matters when a bankruptcy curator who is responsible in handling and administering bankruptcy case is positioned as defendant charged for conducting criminal acts. As stated on Article 234 Verse 2 of Law Number 37 of 2004, a curator who is proven not independent during bankruptcy court may be charged with criminal law. Criminal sanctions for non-independent curators aimed at preventing the curator from committing criminal acts in the course of the execution of the duty and maintenance tasks. Here, the role of criminal law is as a guardian of the norms that exist in the Law on Bankruptcy related to the duties and responsibilities of the curator. In order for a curator or committee before declaring his willingness to accept the duties and responsibilities of the consequences of the bankruptcy verdict or the postponement of the debt obligation obligation (PKPU) really ensure that he will not commit a disgraceful act of.